EVALUATING THE SAFETY AND SECURITY OF EDUCATORS AND LEARNERS AT SOUTH AFRICAN SECONDARY SCHOOLS: CASE STUDIES OF TSHWANE SOUTH, DISTRICT 4 - TD Ngoveni; D Khosa; JT Mofokeng (CV. RADJA PUBLIKA, 2024)
Nelson Mandela, one of the South African Icon, the first democratic government president, regarded education as the key to open any door of life, the view that is embraced within the South African Constitution, 1996, Chapter 2 of the Bill of Rights, Section 29 Sub-section (1) paragraph (a) - (b) stipulates that everyone has the right to free basic education, and the State must, through reasonable measures, make progressively available and accessible. South Africa, just most countries world-wide is still embroiled with less economic growth that impact negatively on most citizens daily lives, something that pushes others to opt to criminal activities, the action that is spreading to schools that was supposed to be a crime free zone area. This study was applied following the qualitative research approach, aided by the case study research design, supported by evaluative research objective. This study was confined to the Gauteng Province, focusing on Tshwane District secondary schools (D4) comprising 04 clusters. The non-probability: Purposive sampling was adopted to select seven (7) school principals, seven (7) deputy principals, and six (6) educators, five (5) learner representatives council members, and 5 SGB chairpersons. In total, thirty (30) participants formed part of this study, and they were all subjected to the unstructured face-to-face interviews. This data collection tool was complimented with literature studies. The inductive Thematic Content Analysis (TCA) was used for data analysis.The findings, based on the criminal activities the schools’ experiences indicate the lack of effective safety and security measures in place, the situation resulting as the predisposing factors for the criminals viewing a school as the soft target to commit robbery. Both educators and learners view themselves vulnerable to criminals, something that makes schools a risky area and not conducive to perform their tasks of educating and learning respectively. As a result, in line with the constitution, 1996, it is concluded and recommended that risk assessment in every school is conducted and provided with security measures that is deemed necessary to promote safety and security for both educators, learners, and everyone within for free and better education as everyone believe in.